2009
DOI: 10.1007/s11605-009-0847-1
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Preoperative Patient Factors to Predict Postoperative Vitamin D Deficiency for Patients Undergoing Gastric Bypass

Abstract: It is important to recognize patients who are at risk for vitamin D deficiency before surgery so that early intervention could be in place to minimize further postoperative deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 14 publications
2
24
0
Order By: Relevance
“…In a study published by Johnson et al, there was a linear decrease in Vit D the longer patients were followed postoperatively, with a corresponding increase in PTH [4]. In examining predictors of postoperative Vit D deficiency, one recent study found preoperative Vit D level to be a significant factor [22]. Other studies implicate Roux limb length as a predictor.…”
Section: Resultsmentioning
confidence: 99%
“…In a study published by Johnson et al, there was a linear decrease in Vit D the longer patients were followed postoperatively, with a corresponding increase in PTH [4]. In examining predictors of postoperative Vit D deficiency, one recent study found preoperative Vit D level to be a significant factor [22]. Other studies implicate Roux limb length as a predictor.…”
Section: Resultsmentioning
confidence: 99%
“…The observation that obesity is associated with below-normal serum 25-hydroxyvitamin D concentrations and/or overt deficiency is not new; however, as obesity prevalence has grown, so have the number of reports in the literature regarding this phenomenon. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Some of the most recent information about low vitamin D status and obesity comes from studies in bariatric surgery patients, reporting low preoperative circulating levels of 25-hydroxyvitamin D. [21][22][23][24][25][26][27][33][34][35][36][37][38] In fact, a recent systematic review of 14 studies with about 1500 patients undergoing bariatric surgical procedures confirmed that obese individuals have serum 25-hydroxyvitamin D levels below 80 nmol l À1 preoperatively. 39 Other investigators have reported that body mass index (BMI) 25,26,[40][41][42][43][44][45][46] and body fat 20,45,…”
Section: Methodsmentioning
confidence: 99%
“…37 Even the RYGB, which is not considered to be a purely malabsorptive procedure, but incorporates both restrictive and malabsorptive elements, presents challenges for vitamin D repletion, given that variable characteristics such as limb length can affect absorption. 24 There are limited data on how best to treat low vitamin D status in bariatric surgery patients, and procedure-specific guidelines are unavailable. A few investigators have reported on the effects of routine vitamin D supplements using cholecalciferol doses found in standard multivitamins (200-400 IU day À1 ), 65,101 and this level of supplementation has typically been inadequate to restore serum 25-hydroxyvitamin D concentrations to normal.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have reported vitamin D deficiencies in obese patients ranging from 41% to 93.8% [6,[10][11][12][13][14][15][16][17]. This wide range may be partly due to the differences in definition of vitamin D deficiency (Table 3).…”
Section: Resultsmentioning
confidence: 98%
“…Studies in post-surgery patients have reported vitamin D deficiencies ranging from 42% to 81% [13][14][15]17,18]. However, there are differences in oral vitamin D supplementation (Table 4).…”
Section: Resultsmentioning
confidence: 99%